Ciudades conscientes para la inserción socio-espacial de los asentamientos informales. - Juan Ignacio Martínez Hurtado (Cuadernos de Geografía de la Universitat de València)
The purpose of this article is to show, through a comparative analysis of the two main policies carried through for the regulation of informal settlements, that there has to be a change of paradigm in the way of understanding cities, to manage their integration in social and spatial terms. A change that reflects these areas as part of the process of shaping of the cities through informality and auto organization. It is necessary to develop a participative urban planning that includes the demands of this sector of the population more vulnerable at the same time that it ensures its rights and commits them to their obligations as citizens, so that any policy can be successful.